Coolest Student Papers at Finland Futures Research Centre 2015–2016 : Tulevaisuuden tutkimuskeskuksen valittuja opiskelijatöitä 2015–2016 - Höyssä, Maria (ed.); Aalto, Hanna-Kaisa (ed.); Kurki, Sofi (ed.); Minkkinen, Matti (ed.); Siivonen, Katriina (ed.); Söderlund, Sari (ed.); Tapio, Petri (ed.); Wilenius, Markku (ed.); Arvonen, Anne (ed.) (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
Welcome to read inspired and inspirational picks from Finland Future Research Centre’s students papers from the study year 2015–16. With this publication, we at the FFRC want to create a channel for making visible the hard work, academic talent and creativity featured in our courses. This Special Issue covers six courses from the international Master’s Degree Programme in Futures Studies (FUTU), two courses organised by Finland Futures Academy (FFA) (taught in Finnish), and the interdisciplinary teamwork course of Sustainability Studies (KEKO) (includes both English and Finnish speaking teams). FUTU, FFA and KEKO studies are all coordinated by the FFRC. In this Special Issue each course forms its own section with an introduction by the teacher(s), followed by the papers.